Enjeux de la formation professionnelle en Suisse Le « modèle » suisse sous la loupe - Bonoli, Lorenzo; Berger, Jean-Louis; Lamamra, Nadia (Seismo, 2019)
The Swiss vocational education and training model is at the heart of an unprecedented enthusiasm. Both in Switzerland and abroad, it is praised for its management based on a public-private partnership, for its ability to integrate a large number of young people in beyond mandatory education and, finally, for the quality of the training provided which is in line with the labour market needs. However, these assets may hide the high complexity of this model and the challenges it currently faces and will face in the future. Gathering thirteen chapters from specialists, this book offers a close look at the Swiss vocational education and training model. It provides the factual information and the theoretical tools necessary to understand its complexity and identify its major challenges.